Pengaruh pemberian fluid warmer pada infus terhadap suhu tubuh pada pasien dengan anestesi spinal - Mulyani, Tri; Sutrisno, Sutrisno; Indriyati, Indriyati (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Perioperative hypothermia is a common complication in patients undergoing spinal anesthesia, with a core body temperature below 36°C. This condition can cause various serious consequences, such as nervous system disorders, decreased blood pressure, and even death. Purpose: To determine the effect of intravenous fluid warmers on body temperature in patients undergoing spinal anesthesia. Method: This quantitative, pre-experimental study used a one-group pretest and posttest design. The sample consisted of 48 patients selected using purposive sampling. The intervention consisted of warm intravenous fluids using a fluid warmer (ANIMEC). Body temperature was measured before and after the intervention using a thermometer. Results: The study showed that before the intervention, the majority of participants experienced mild hypothermia (33°C–35.9°C) (35 participants (72.9%) and moderate hypothermia (30°C–32.9°C) (13 participants (27.1%). After administration of a fluid warmer, there was a significant increase in body temperature, with a mean final temperature of 36.60°C (SD=0.3155). The Wilcoxon Signed-Rank Test showed a p-value of 0.001 <0.05. Conclusion: The administration of a fluid warmer during infusion has an effect on the body temperature of spinal anesthesia patients. Keywords: Body Temperature; Fluid Warmer; Hypothermia; Perioperative; Spinal Anesthesia. Pendahuluan: Hipotermia perioperatif merupakan komplikasi yang sering terjadi pada pasien pasca anestesi spinal, dengan suhu inti tubuh di bawah 36°C. Kondisi ini dapat menyebabkan berbagai dampak serius, seperti gangguan sistem saraf, penurunan tekanan darah, hingga kematian. Tujuan: Untuk mengetahui pengaruh pemberian fluid warmer pada infus terhadap suhu tubuh pasien dengan anestesi spinal. Metode: Penelitian kuantitatif dengan jenis pre eksperimental menggunakan one group pretest and posttest design. Sampel terdiri dari 48 pasien yang dipilih secara purposive sampling. Intervensi berupa pemberian cairan infus hangat menggunakan fluid warmer (ANIMEC). Suhu tubuh diukur sebelum dan setelah intervensi menggunakan termometer. Hasil: Penelitian menunjukkan bahwa sebelum intervensi, mayoritas partisipan mengalami hipotermia ringan (33°C–35,9°C) sebanyak 35 orang (72,9%) dan hipotermia sedang (30°C–32,9°C) sebanyak 13 orang (27,1%). Setelah pemberian fluid warmer, terjadi peningkatan suhu tubuh yang signifikan, dengan rata-rata suhu akhir 36,60°C (SD=0,3155). Uji Wilcoxon Signed-Rank Test menunjukkan (p value 0,001 < 0,05. Simpulan: Pemberian fluid warmer pada infus berpengaruh terhadap suhu tubuh pasien anestesi spinal. Kata Kunci: Anestesi Spinal; Fluid Warmer; Hipotermia; Perioperatif; Suhu Tubuh.